Spontaneous perinephric hematoma in an emergency department patient with flank pain: A case report - Amna Nawaz; Denise Elizondo; Rebecca G. Theophanous (JEM Reports)
Background: Perinephric hematomas are defined by hemorrhage originating from the kidney parenchyma into the subcapsular and perirenal spaces. Spontaneous perinephric hematomas are rare and usually occur due to an underlying renal mass, vascular abnormality, coagulation disorder, or inflammatory disorder. The classic clinical presentation includes acute flank pain, hemorrhagic shock, and detection of a renal mass. Diagnosis is by computed tomography (CT), ultrasound, or angiography. Case report: A 74-year-old male with coronary artery disease, severe heart failure, and atrial fibrillation/flutter on apixaban presented to the emergency department (ED) with left-sided abdominal and back pain for two weeks. He denied urinary symptoms, fever, or vomiting. The patient was hypotensive with low hemoglobin (8.9g/dL), thus he received blood transfusions and apixaban reversal for hemorrhagic shock. CT scan diagnosed a 10x9 cm perinephric hematoma, and he was transferred to our hospital’s ED. Point-of-care ultrasound demonstrated a left perinephric hematoma and clotted blood in the splenorenal recess. Urology and interventional radiology (IR) were consulted, with emergent transport to IR for angiogram and left coil embolization then intensive care unit admission. Why should an emergency medicine physician be aware of this: This case describes important diagnostic testing and bedside ultrasound utility in expediting care for patients with renal pathology. It describes a case of spontaneous renal hemorrhage and management steps including IR embolization, urology involvement, and evaluation for surgical intervention. Finally, we emphasize potential serious complications including chronic renal failure, pyelonephritis, renal obstruction, and permanent kidney distortion if disease is not recognized and treated early.